Multi-stage, charge conversional, stimuli-responsive nanogels for therapeutic protein delivery. (19th August 2015) - Zhang, Xuejiao; Zhang, Kai; Haag, Rainer
Abstract : A two-stage charge conversional nanogel with ATP/pH-sensitivity was generated. The first-stage charge conversion at tumor extracellular pH can enhance the tumor cellular uptake and the second-stage charge conversion in the acidic intracellular organelles (endo/lysosome) can result in the endosomal escape. Abstract : A boronate ester crosslinked zwitterionic nanogel (NGCA) with ATP/pH-sensitivity has been developed with an inverse nanoprecipitation technique to achieve a two-stage charge conversion that responds to tumor extracellular conditions (pH 6.5–6.8) and an intracellular acidic environment (pH 5–6). Cationic cytochrome C (CC), a therapeutic protein, has been encapsulated into NGCA through inverse nanoprecipitation via electrostatic interactions to form protein-loaded nanogel (NGCA-CC). By adjusting the ratio of the amino and carboxyl groups in the nanogels, negatively charged nanogels that are safer under physiological conditions (pH 7.4) can convert their surface charge to positive at tumor extracellular pH, which enhance their cellular uptake efficiency. The citraconic amide formed from citraconic anhydride and amine can be cleaved in the intracellular acidic organelles to expose more amino groups and facilitate endosomal escape. The release of CC is accelerated in the presence of 5 mM ATP or under acidic conditions. Confocal laser scanning microscopy (CLSM) and flow cytometry have shown that NGCA-CC's cell uptake is higher at pH 6.5 than at pH 7.4. MTT and real-time cell analysis (RTCA) have illustrated that there is more toxicity at pH 6.5 than at pH 7.4. The apoptosis process induced by CC was determined by flow cytometry.